Implementasi Penegakan Hukum dalam Tindak Pidana yang Dilakukan oleh Mafia Tanah di Jawa Timur - Rizki, Rafi Dwi; Sutrisno, Sutrisno (Universitas Semarang, 2025)
This research aims to analyze law enforcement in criminal acts committed by the land mafia in the East Java Regional Police. The urgency of this research is due to the increasing number of land mafia cases in Indonesia due to inadequate regulations and supervision. In compiling the research, the author used an empirical juridical research approach using primary data obtained from interviews, observations, and document processing at the East Java Regional Police by the Anti-Land Mafia Task Force, and secondary data obtained from official documents, books and statutory regulations. invitation. The results of this research indicate that there is a need for synergy by creating a Memorandum of Understanding between the Ministry of ATR/BPN regarding land crimes in order to facilitate the investigation and law enforcement process related to land crimes. Keywords: Law enforcement, crime, land mafia.